Branding resources: extractive communities, industrial brandscapes and themed environments. (April 2015) - Scott, Rebecca; Bennett, Elizabeth
As the labour process is mechanized and Fordist social contracts between company and workers erode, extractive communities bear increased costs while receiving fewer benefits. The authors use two case studies to elucidate how processes that characterize post-industrial culture elsewhere are now transforming the working landscapes of rural mining and timbering communities. Companies draw on branding techniques familiar to other contexts to evoke markets where none exist, and to link production practices with particular forms of identity. These branding strategies at the site of production attempt to simulate the paternalistic culture of a company town, in a themed environment that identifies the company with both locale and nation. These techniques allowed both companies in this article to extend temporary legitimacy in their practices, creating a sense of continuity despite the radical rearrangement and intensification of mining and timbering practices.